Pengaruh Pelaksanaan Akreditasi Puskesmas terhadap Kepuasan Pasien (Media Kesehatan Masyarakat Indonesia, 2019)
Since the enactment of the National Health Insurance (JKN) policy, all Primary Health Care in Indonesiamust follow accreditation. Through accreditation, it is expected that the quality of Primary Health Care serviceswill increase, one of which can be seen from the increase in patient satisfaction. This study was conducted toanalyze the effect of accreditation on patient satisfaction. The study was conducted on 90 Primary Health Carepatients who had visited the Primary Health Care before and after accreditation. Data retrieval has been donecrossectionally. The paired-sample T test was conducted to see the significance of differences in satisfactionscores before and after accreditation. The results showed that there were significant differences in satisfactionscores between before and after accreditation for the dimensions of responsiveness, credibility, competence,communication, security, access, courtesy, understanding customer and tangibles. In the reliability dimensionno significant differences were found. While specifically for the cutomer understanding dimension there was adecrease in satisfaction scores after accreditation. Therefore, it is important for Primary Health Care to improvetheir service systems, especially related to fulfilling service promises that have been set as quality objectives.Dissemination of information to the public must be improved, so that the public becomes aware of the existence ofprograms run by the Primary Health Care, such as accreditation.
Keywords: Akreditasi; kepuasan; mutu; pasien; puskesmas